PERNIKAHAN DENGAN PEKERJA SEKS KOMERSIAL DI LOKALISASI MOROSENENG PERSPEKTIF HUKUM ISLAM - Muhammad Fikri Izzuddin (State Islamic University (UIN) of Sunan Ampel, 2017)
This is a field research that highlights the marriage with commercial sex workers in Moroseneng localization of Benowo, Surabaya and its legal status. The study concludes that there are three cases of marriage in the localization. The first, the wife is still active as a commercial sex worker for two months after her marriage took place. The second, the wife had repented before the marriage took place, and the third, the wife had stopped after her marriage. This marriage is held as in general, that are by fulfilling the marriage pillars, namely the prospective husband and wife, marriage guardian, two witnesses and ijab qabul, and reinforced by a certificate of marriage from the local village office (kelurahan). Muslim scholars differ on the law of marrying adulteress women, there is an absolute allowance and there are also some conditionals. The School of Imam Hanafi, Imam Shafi'I’ and Imam Maliki agree that the law of marriage is permissible because there is no prohibition to marry an adulterous woman. While Imam Hanbali requires adulterous women to marry should repent first. Thus, marriage with commercial sex workers in Moroseneng localization of Benowo Sub-District of Surabaya City is valid, let alone the pillars have been fulfilled. In addition, the underlyed reason for the marriage is the desire to help commercial sex workers from her prostitution environment and foster good housekeeping.